VD_FINDINFO HC / 2012 / 568 vom 23. August 2012 - VD Tribunal cantonal (2012)
LIQUIDATION OFFICIELLE, PROCÉDURE SOMMAIRE, DÉVOLUTION DE LA SUCCESSION | 593 al. 2 CC, 248 let. e CPC (CH), 109 al. 3 CDPJ, 152 CDPJ, 153 CDPJ